Efektivitas Tayangan Humor Dalam Menurunkan Stres Pada Masa Rehabilitasi Bagi Penyalahguna Narkoba Di Rutan Makassar - Agni Imaniah Rahmah; Sitti Murdiana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The purpose of this study was to determine the effectiveness of humor in reducing stress during the rehabilitation period for drug abusers in the Makassar Detention Center. This research is using experimental method. Participants in this study were 18 drug abusers undergoing rehabilitation at the Makassar Detention Center and divided into 2 groups, 9 experimental groups and 9 control groups. The experimental design in this study was a quasi-experimental design with a pretest-posttest control group. The data analysis technique used the Wilcoxon signed-rank test. The analysis test showed a significant result of p = 0.012 (p <0.05) which indicated that there was a significant difference between the experimental group and the control group. The results of hypothesis testing in this study stated that giving treatment in the form of humor shows was effective in reducing stress for drug abusers undergoing rehabilitation at the Makassar Detention Center